Holiday rural teachers' skill development programme and their geometry knowledge (2009)
Geometry being an important aspect of Mathematics at all levels of education demands in - depth knowledge from mathematics teachers for effectiveness of its teaching ince knowledge is dynamic, rural teachers need to up - date their knowledge both on the subject they teach and the pedagogy found to be effective. This study therefore, investigated the impact of skill development programme organized for rural Primary School teachers on their Geometry context knowledge. The effects of years of teaching and highest qualification on Geometry content knowledge of the teachers were also investigated The study being an experimental tudy adopted single group pretest-post test research design. Two hundred and orty one rural public schools participated in the study. A teacher was randomly selected from each of the two hundred and forty one public primary schools existing in the three selected Rural Local Government Areas in Oyo State. The instrument used for data collection was Geometry Content Test (KR20= ). The data collected was analysed using paired t - test and analysis of covariance. It was found in the study that the skill development programme has significant paired t - test and analysis of covariance. It was found in the study that the skill development programme has significant main effect on rural primary school teachers' knowledge of Geometry content (P<0.05). Teacher's years of teaching and highest educational qualification were found not to have significant effect on Geometry Content knowledge. Adequate knowledge of Geometry is needed to promote effective mathematics teaching in public primary schools. Such adequacy can only be ensured through periodic skill development training programme for teachers. It is therefore imperative to equip all rural public primary school teachers with adequate Geometry Content Knowledge via skill development programme and until this is done,inadequacy found in geometry teaching in primary schools will remain a menace